The concept of morals in the book of ayyuhal walad: Relevance to moral education in daily life in pesantren - Rianda Ayu Ritnaning Tias; Azam Makarim; Rahmah As Sa'idah (At Turots: Jurnal Pendidikan Islam, 2025)
Moral education has a central role in individual character building, especially in Islamic education. However, reality shows the moral decline of the younger generation, including in the educational environment. One of the efforts to overcome this problem is by implementing moral values contained in the works of classical scholars, one of which is the book of Ayyuhal Walad by Imam Al-Ghazali. This study aims to examine the concept of morals in the book of Ayyuhal Walad and analyze its relevance and actualization in the daily lives of santri in pesantren. This research uses a qualitative approach with a type of library research combined with observation, interviews, and documentation at Muhammadiyah Boarding School Bantul 1 (MBS Muhiba), Yogyakarta. The main data comes from the book Ayyuhal Walad and is reinforced with field data from the activities of the santri in the pesantren. The results showed that in the book of Ayyuhal Walad there are six main moral concepts: (1) morals in worshiping Allah, (2) morals towards fellow human beings, (3) morals in studying, (4) morals of educators, (5) morals towards teachers, and (6) guarding oneself from despicable morals. The implementation of these values is reflected in the daily lives of students through the habit of sincere worship, mutual respect, maintaining adab to teachers, enthusiasm for studying, and social behavior based on Islamic values.